Defense Strategy for Inland Waters, Indonesian Archipelagic Sea Lanes II to Prevent Non-Military Threats in the Capital of the New Nation - Syaeful Bakhri; Harjo Susmoro; Beni Rudiawan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The transfer of the State Capital (KN) from Jakarta to East Kalimantan Province in North Penajam Paser Regency has now been determined by the government with the enactment of Law No. 3 of 2022 concerning the State Capital. In the law, it is explained that one of the functions of IKN is as a Center of gravity (CoG), namely symbolizing the sovereignty of a country, therefore IKN is a national vital object to maintain its existence from threats, therefore IKN requires a system and strategy to protect it in this case. non-military threat. In this thesis the researcher used a descriptive qualitative research method with the formulation of the problem from the problem statement to be able to protect the IKN from non-military threats in the Indonesian Archipelagic Sea Lanes (ALKI) II. The results of the research that the researchers got were the significance of non-military threats in the inland waters defense area in ALKI II, giving rise to an urgency to develop a new IKN defense strategy that can ward off non-military threats in the planning stages of the IKN transfer. Which then the researcher concluded that in efforts to move the IKN it is important to analyze the defense of inland waters in ALKI II with the aim of maintaining the defense of IKN with an inland waters defense strategy, in order to realize national defense from non-military threats.